Minimally invasive surgery and its impact on 30‐day postoperative complications, unplanned readmissions and mortality. Issue 10 (20th June 2017) - Sood, A.; Meyer, C. P.; Abdollah, F.; Sammon, J. D.; Sun, M.; Lipsitz, S. R.; Hollis, M.; Weissman, J. S.; Menon, M.; Trinh, Q.‐D.
Abstract: Background: A critical appraisal of the benefits of minimally invasive surgery (MIS) is needed, but is lacking. This study examined the associations between MIS and 30‐day postoperative outcomes including complications graded according to the Clavien–Dindo classification, unplanned readmissions, hospital stay and mortality for five common surgical procedures. Methods: Patients undergoing appendicectomy, colectomy, inguinal hernia repair, hysterectomy and prostatectomy were identified in the American College of Surgeons National Surgical Quality Improvement Program database. Non‐parsimonious propensity score methods were used to construct procedure‐specific matched‐pair cohorts that reduced baseline differences between patients who underwent MIS and those who did not. Bonferroni correction for multiple comparisons was applied and P < 0·006 was considered significant. Results: Of the 532 287 patients identified, 53·8 per cent underwent MIS. Propensity score matching yielded an overall sample of 327 736 patients (appendicectomy 46 688, colectomy 152 114, inguinal hernia repair 59 066, hysterectomy 59 066, prostatectomy 10 802). Within the procedure‐specific matched pairs, MIS was associated with significantly lower odds of Clavien–Dindo grade I–II, III and IV complications ( P ≤ 0·004), unplanned readmissions ( P < 0·001) and reduced hospital stay ( P < 0·001) in four of the five procedures studied, with the exception of inguinal hernia repair. The odds of death were lower in patients undergoing MIS colectomy ( P < 0·001), hysterectomy ( P = 0·002) and appendicectomy ( P = 0·002). Conclusion: MIS was associated with significantly fewer 30‐day postoperative complications, unplanned readmissions and deaths, as well as shorter hospital stay, in patients undergoing colectomy, prostatectomy, hysterectomy or appendicectomy. No benefits were noted for inguinal hernia repair. Abstract : Generally better outcomes after laparoscopic surgery